Socio-political attitudes 1975 - Ekehammar, Bo (Stockholm University, 1987)
The central aim of the study is looking at various aspects of political perception as a function of socio-political ideology. The politically percepted objects consists mainly of political parties, party-leaders and countries. The measurement of political perception is made through multi-dimensional scaling, semantic differential and political differential. Political ideology is operationalized through party affiliation and socio-political attitude (measured with a specially designed scale). From these data some indexes are generated on the individual level for cognitive articulation and cognitive differentiation which then are related to the individual's socio-political ideology. The first part of the study contains questions about attitudes to various phenomena in society, socio-economical questions, party preferences (own, parents), education of relatives, estimation of: left-right, religiosity and extremism. The second part (where the sample is a subgroup of the first part's sample) contains the same questions plus estimations of: some Swedish politicians, countries (Sweden, USA, the Soviet Union and China) and Swedish political parties.

The central aim of the study is looking at various aspects of political perception as a function of socio-political ideology. The politically percepted objects consists mainly of political parties, party-leaders and countries. The measurement of political perception is made through multi-dimensional scaling, semantic differential and political differential. Political ideology is operationalized through party affiliation and socio-political attitude (measured with a specially designed scale). From these data some indexes are generated on the individual level for cognitive articulation and cognitive differentiation which then are related to the individual's socio-political ideology. The first part of the study contains questions about attitudes to various phenomena in society, socio-economical questions, party preferences (own, parents), education of relatives, estimation of: left-right, religiosity and extremism. The second part (where the sample is a subgroup of the first part's sample) contains the same questions plus estimations of: some Swedish politicians, countries (Sweden, USA, the Soviet Union and China) and Swedish political parties.
Sociopolitiska attityder 1975
Keywords: Political behaviour and attitudes; Politiska beteenden och attityder; Youth; Ungdomar; Social behaviour and attitudes; Socialt beteende och attityder; Social Sciences; Samhällsvetenskap